2021
DOI: 10.1186/s12885-021-08155-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial DNA abnormalities provide mechanistic insight and predict reactive oxygen species-stimulating drug efficacy

Abstract: Background Associations between mitochondrial genetic abnormalities (variations and copy number, i.e. mtDNAcn, change) and elevated ROS have been reported in cancer compared to normal cells. Since excessive levels of ROS can trigger apoptosis, treating cancer cells with ROS-stimulating agents may enhance their death. This study aimed to investigate the link between baseline ROS levels and mitochondrial genetic abnormalities, and how mtDNA abnormalities might be used to predict cancer cells’ res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Cancer cells tend to possess high levels of adaptive antioxidant system and highly reactive oxygen species (ROS), and increased levels of reactive oxygen species disrupt the initial redox homeostasis, which promotes tumor proliferation, metastasis and drug resistance ( 71 , 72 ). Although high ROS levels can induce apoptosis of cancer cells, their prolonged activation inevitably reduces the efficacy of chemotherapy due to the establishment of drug resistance ( 73 , 74 ). Combination therapies to combat chemotherapy resistance have been extensively studied in clinical trials, while cancer treatment strategies that modulate ROS to modify the tumor microenvironment urgently need more in-depth research ( 75 ).…”
Section: Natural Products Possess Anti-tumor Functionmentioning
confidence: 99%
“…Cancer cells tend to possess high levels of adaptive antioxidant system and highly reactive oxygen species (ROS), and increased levels of reactive oxygen species disrupt the initial redox homeostasis, which promotes tumor proliferation, metastasis and drug resistance ( 71 , 72 ). Although high ROS levels can induce apoptosis of cancer cells, their prolonged activation inevitably reduces the efficacy of chemotherapy due to the establishment of drug resistance ( 73 , 74 ). Combination therapies to combat chemotherapy resistance have been extensively studied in clinical trials, while cancer treatment strategies that modulate ROS to modify the tumor microenvironment urgently need more in-depth research ( 75 ).…”
Section: Natural Products Possess Anti-tumor Functionmentioning
confidence: 99%
“…Our laboratory recently demonstrated that DFF40 deficiency in Jurkat T cells induced a higher redox state at basal state [8]. Recently, it was shown that elevated ROS production in cancer cells was associated with higher mtDNA copy number (mtDNAcn) [19]. These results brought our laboratory to suggest a role of DFF40 in preserving mitochondria homeostasis and function.…”
Section: Introductionmentioning
confidence: 84%
“…deficient Jurkat cells had higher ROS production at basal state [8]. Recently, it was shown that Caco-2 cancer cells exhibiting higher ROS production at basal state had higher mtDNAcn [19]. We thus sought to determine the impact of DFF40 deficiency in Jurkat and HeLa cells on mtDNAcn and mitochondrial mass (Fig.…”
Section: Dff40 Deficiency Upregulates Mitochondrial Dna Mitochondrial...mentioning
confidence: 99%
“…Mitochondria is membrane-bound cell organelles that are considered a primary intracellular site of ROS generation, importantly, the high levels of ROS can trigger apoptosis, which is what triggers mitochondrial abnormalities. 22, 23 Plumbagin data on pancreatic cancer cells showed that it activated apoptosis through the induction of ROS production along with upregulation of cleaved caspase 3 and caspase 9 and downregulation of Bcl-2 protein. 24 The caspase cascade is the key signaling pathway that triggered apoptosis.…”
Section: Discussionmentioning
confidence: 99%